Implementation of an e-learning model to build capacity of providers within a cervical cancer prevention programme in Africa: a successful experience in Cameroon. Issue 1 (April 2020) - Fokom Domgue, Joel; Baker, Ellen; Manjuh, Florence; Lopez Varon, Melissa; Elit, Lorraine; Welty, Edith; Milbourne, Andrea; Starr, Ellen; Welty, Thomas; Parham, Groesbeck P; Ramondetta, Lois; Randall, Thomas; et al.
Abstract: Background: In a context where specialist physicians are lacking and usually inaccessible, trained nurses can provide affordable cervical cancer screening and management services to women. Considering the rapid development of emerging cervical cancer prevention, diagnostic, and treatment procedures, nurses need to update their skills and knowledge regularly in the most appropriate way possible. Furthermore, the management of difficult cases in these settings is challenging, since many patients referred for specialty care cannot afford those services and must continue their care with local health providers. In this study, we applied and reviewed the telementoring scheme ECHO (Extension for Community Health Outcomes) designed to provide support for the Women's Health Program of the Cameroon Baptist Convention Health Services, a programme run by trained nurses that provides lower-cost cervical cancer screening and treatment to women in Cameroon. Methods: Since June 2018, the Women's Health Program of the Cameroon Baptist Convention Health Services has benefited from the expertise of specialist consultants in the USA, Canada, Europe, and Africa through monthly telementoring meetings using the ECHO model to review clinical cases and provide tailored didactic lectures. During each ECHO teleconference, clinicians from Cameroon and other African countries present two clinical cases to experts who provide recommendations for management, and experts give a didactic lecture on a topic relevant to providers, including cervical cancer prevention. In December, 2018, we administered a survey to Women's Health Program providers who had attended at least one ECHO session to collect data on baseline characteristics, previous training, and programme satisfaction. Findings: Between June, 2018, and August, 2019, 28 clinical cases were reviewed and 15 lectures presented. The number of participants in these ECHO sessions has increased from 5–10 to about 40–45. 16 nurses (median age 32 years [range 25–55 years]) completed the satisfaction survey; 15 were women (94%). Most participants had previously been trained to perform cervical cancer counselling (15 [94%]), to screen for cervical cancer with visual methods or to collect specimens for HPV testing (15 [94%]), to perform cervical biopsies (12 [75%]), and to treat with cryotherapy or thermal coagulation (13 [82%]). All respondents enjoyed the opportunity of learning with peers, 10 (63%) reported that ECHO sessions increased their ability to access specialty care, 14 (88%) reported that these sessions have improved the coordination of care, and 12 (75·0%) that these sessions have improved the quality of patients care. Most clinicians had adopted best-practice care following these sessions (12 [75%]), or developed additional clinical skills (10 [63%]). Interpretation: Within the Cameroon Baptist Convention Health Services Women's Health Program, results from Project ECHO have shown improved clinical skills and knowledge for providers, and enhanced quality of care for patients. This simple and inexpensive tool has the potential to foster quality improvement of cervical cancer prevention programmes in resource-limited countries. After the success of the programme in Cameroon, ten other African countries have joined the ECHO sessions. Funding: None